SIMILARITY RELATIONSHIPS AMONG GREEK MIDDLE MIOCENE TO EARLY - MIDDLE PLEISTOCENE MAMMAL ASSEMBLAGES - Kostopoulos, D. S.; Koufos, G. D. (Bulletin of the Geological Society of Greece, 2007)
The Greek fossil record of small and large mammal Local Faunal Assemblages is studied and compared by means of cluster analysis techniques using Jaccard similarity index and unweighted pair-group method. The analysis allow recognizing a good arrangement of the Greek LFAs according to time and a main cluster gap, corresponding to an important faunal renewal that, however, is not synchronous in the large and small mammal community. Minor groupings of large mammal faunas seem also to fit with main climatic trends, whereas the small mammal assemblage appears to undergo longer periods oftaxonomic stability